(untitled) (Research, Society and Development, 2023)
This research aimed to estimate the factors associated with the risk of falls in hospitalized patients in a teaching hospital through a descriptive analytical study with a quantitative approach. Data were collected from fall notifications recorded in the VIGIHOSP surveillance system and a structured questionnaire, which included sociodemographic variables, health conditions, fall risk assessment, and multiprofessional monitoring. Records of 42 falls between 2018 (the year when the surveillance system was implemented) and the first semester of 2021 were included. Regarding sociodemographic variables, age over 70 years, male gender, non-white individuals, and informal workers showed statistical significance, as well as clinical hospitalization, hemodynamic changes before and after the fall, comorbidities, fall risk assessments, the use of devices, and clinical outcomes including transfer and death. In light of these results, it is believed that early detection and the elimination of fall risks can ensure the provision of health promotion and injury prevention strategies.